2004
DOI: 10.1007/s00423-003-0429-8
|View full text |Cite
|
Sign up to set email alerts
|

Decreased collagen type�I/III ratio in patients with recurring hernia after implantation of alloplastic prostheses

Abstract: The present study confirms the importance of a biological approach, next to technical aspects, to the understanding of the pathogenesis of recurrent hernia formation and underscores the presence of a disturbed scarring process. The composition of scar tissue with a lowered collagen type I/III ratio and, therefore, reduced tensile strength may be a major contribution to hernia recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(39 citation statements)
references
References 26 publications
2
35
0
2
Order By: Relevance
“…27 Multiple studies have shown decreased collagen I/III ratios in mature skin scars from patients with either primary or recurrent incisional hernias compared with mature abdominal skin scars from patients without hernias 23, 2831 and in periprosthetic scar of recurrent inguinal and incisional hernias. 32 A common link between all hernias has been found by some studies including differing etiologies. Ozdemir et al 33 included indirect, direct, and incisional hernias in their evaluation of copper and zinc levels.…”
Section: Evidence For Collagenopathies In Herniasmentioning
confidence: 94%
“…27 Multiple studies have shown decreased collagen I/III ratios in mature skin scars from patients with either primary or recurrent incisional hernias compared with mature abdominal skin scars from patients without hernias 23, 2831 and in periprosthetic scar of recurrent inguinal and incisional hernias. 32 A common link between all hernias has been found by some studies including differing etiologies. Ozdemir et al 33 included indirect, direct, and incisional hernias in their evaluation of copper and zinc levels.…”
Section: Evidence For Collagenopathies In Herniasmentioning
confidence: 94%
“…Though a high amount of collagen type III is related to inflammation and the early phase of wound healing, a similar pattern is also seen in patients with disturbed wound-healing process [25] or in the scar of chronic foreign body reaction around meshes [25,26].…”
Section: Discussionmentioning
confidence: 93%
“…However, the mesh-induced inflammatory reaction frequently causes complications, including seroma formation, mesh shrinkage and migration, adhesion, infection, and pain. [26]…”
Section: Discussionmentioning
confidence: 99%